OtherScope - the virtual microscope - can the real learning experiences in practical science be simulated?. (1st January 2000) - Velle, Linda la; Watson, Kate; Nichol, Jon
This paper discusses the nature, advantages and disadvantages, uses, and future application of simulation programs in science education. A recently conducted evaluation of a novel simulation currently under development in a web-based format is presented, and the paper concludes with a discussion of the evolving pedagogy of the new information and communications technologies in general and simulation in particular. It concludes that simulation is a form of knowledge representation in its own right. As such, it can be an alternative to, as well as an imitation of, lab-based practical work.